Activation of PPAR alfa and PPAR beta/delta regulates Sertoli cell metabolism. - Regueira, Mariana (2014)
The purpose of this study was to evaluate the existence of a possible simultaneous regulation of fatty acid (FA) metabolism and lactate production by PPAR a and PPAR b/d activation in Sertoli cells (SC). SC cultures obtained from 20-day-old rats were incubated with WY14643 or GW0742-pharmacological activators of PPAR alfa and PPAR beta/delta respectively. The fatty acid transporter CD36, carnitine palmitoyltransferase 1, long- and medium-chain 3-hydroxyacyl-CoA dehydrogenases mRNA levels were analyzed. An increase in the above-mentioned genes in response to activation of both nuclear receptors was observed. Additionally, PPAR b/d activation increased lactate production as a consequence of increased pyruvate availability by inhibiting the Pyruvate Dehydrogenase Complex. Altogether, these results suggest that in SC, PPAR a activation participates in the regulation of FA metabolism. On the other hand, PPAR b/d activation regulates FA metabolism and lactate production ensuring simultaneously the energetic metabolism for SC and germ cells.